2000
DOI: 10.1046/j.1523-1755.2000.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine induces different responses in human epithelial, endothelial and fibroblast cell cultures

Abstract: Our results demonstrate that cyclosporine exhibits an antiproliferative effect on endothelial and epithelial cells. This effect is associated with induction of apoptosis probably via nitric oxide up-regulation in epithelial cell cultures. Cyclosporine treatment induces ECM accumulation by increasing collagen synthesis in endothelial and epithelial cells and reducing its degradation by up-regulating TIMP-1 expression in fibroblasts. We conclude that cyclosporine affects cell types differently and that the disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 30 publications
5
62
0
1
Order By: Relevance
“…Another study in neuronal cells also observed apoptosis inhibition (but sensitisation for necrosis) by cypD overexpression [123]. Moreover, there is accumulating evidence that cyclosporin A can induce apoptosis in certain cells [124][125][126][127]. In fact, the clinical use of CsA is still limited by its potential toxicity [128,129] and a specific inhibition of the PT-pore as observed with cypD [120,122] would be therapeutically of high interest.…”
Section: Overexpression Studies On Cypdmentioning
confidence: 92%
“…Another study in neuronal cells also observed apoptosis inhibition (but sensitisation for necrosis) by cypD overexpression [123]. Moreover, there is accumulating evidence that cyclosporin A can induce apoptosis in certain cells [124][125][126][127]. In fact, the clinical use of CsA is still limited by its potential toxicity [128,129] and a specific inhibition of the PT-pore as observed with cypD [120,122] would be therapeutically of high interest.…”
Section: Overexpression Studies On Cypdmentioning
confidence: 92%
“…However, the effect upon nonlymphoid cells appears to be less straightforward, with variable effects upon epithelial cell proliferation between different organ systems. While anti-proliferative to renal tubular epithelium and implicated in the pathogenesis of tubular fibrosis observed in chronic renal allograft rejection (56), cyclosporin exerts a proliferative effect upon airway epithelium in rat tracheal isografts (57). In addition, cyclosporin may have direct effects upon epithelium (58).…”
mentioning
confidence: 99%
“…Cyclosporine may have adverse effects on the grafted vessels, resulting in accelerated atherosclerosis (Esposito et al, 2000). We did not see differences between the cyclosporine-treated and non-treated groups during the observation period.…”
Section: Discussionmentioning
confidence: 53%